2010
DOI: 10.1097/qai.0b013e3181e7744e
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective Study on the Critical Factors for Retaining Patients on Antiretroviral Therapy in KwaZulu-Natal, South Africa

Abstract: The analysis has identified the conditions influencing retention of ART patients in KZN. This has provided a method to estimate absorption capacity of the ART delivery sites, which is of added value for a sustainable expansion of the ART coverage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 31 publications
2
16
0
Order By: Relevance
“…Factors such as sex, age, and education level were frequently cited in these articles. For example, a number of articles noted that male sex was associated with an increased risk of attrition from care [28, 3235, 37], as was younger age [27, 30, 34], and lower levels of education [28, 36, 39]. …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Factors such as sex, age, and education level were frequently cited in these articles. For example, a number of articles noted that male sex was associated with an increased risk of attrition from care [28, 3235, 37], as was younger age [27, 30, 34], and lower levels of education [28, 36, 39]. …”
Section: Resultsmentioning
confidence: 99%
“…This finding was replicated by Palombi et al [38], and likewise Koole et al [30] who found that retention rates decreased as the number of years the clinic had been in operation increased. Likewise, Vella et al [35] noted that clinics with part-time (compared to full-time) nursing and medical staff demonstrated poorer retention rates. Mutasa-Apollo et al [32] also note that those initiating medication at primary healthcare facilities (compared to district hospitals) were more likely to remain retained, and the authors suggest this is likely because rural patients would travel to urban hospitals to initiate treatment under medical specialists and then likely transfer back to rural facilities.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that Namibia does not educate its own physicians and pharmacists and is experiencing rapid nurse turnover, the opportunity for long-term HCP relationships may be affected (UNGASS, 2010). The lack of a full-time senior professional nurse or doctor was a significant risk factor for retention on ARVs in South Africa (Vella, et al, 2010). These results emphasize the importance of both HCP availability and quality of the patient-provider relationship (Aragones, Sanchez, Campos, & Perez, 2011; Kagee, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…In September 2016, South Africa implemented universal ART eligibility, extending ART eligibility to all 7.1 million HIV-positive South Africans. While the benefits of universal HIV treatment are evident, concerns that further expansion of ART programmes may compromise quality of care [3][4][5][6][7] make it essential to monitor trends in the mortality of patients on ART.…”
Section: Introductionmentioning
confidence: 99%